2001
DOI: 10.1161/01.str.32.8.1786
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Disorders in Children With Moyamoya Syndrome

Abstract: Background and Purpose — Moyamoya syndrome is an uncommon chronic occlusive cerebrovascular disease in children. The origin of moyamoya syndrome remains undetermined. The role of the prothrombotic disorders contributing to its pathogenesis has not been completely elucidated. The purpose of this study was to determine the frequency of prothrombotic disorders in a pediatric population with moyamoya syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 62 publications
2
64
1
Order By: Relevance
“…35 A study from 2002 to 2006 states the incidence rate is now up to 0.94 patients per 100,000 people, with a prevalence of 10.5 patients per 100,000. 5 Moyamoya disease in this survey was more prevalent in women than men, with a female to male ratio of 1.8:1. 35 The survey showed the highest prevalence for males at ages [10][11][12][13][14] and smaller peaks at 35-39 and 55-59.…”
Section: Epidemiologymentioning
confidence: 63%
See 1 more Smart Citation
“…35 A study from 2002 to 2006 states the incidence rate is now up to 0.94 patients per 100,000 people, with a prevalence of 10.5 patients per 100,000. 5 Moyamoya disease in this survey was more prevalent in women than men, with a female to male ratio of 1.8:1. 35 The survey showed the highest prevalence for males at ages [10][11][12][13][14] and smaller peaks at 35-39 and 55-59.…”
Section: Epidemiologymentioning
confidence: 63%
“…57 Protein S deficiency, lupus anticoagulant, and anticardiolipin antibodies have been found in other cases. 5 Anticardiolipin antibody binds to phosphatidyl-glycerol, a component of the plasma membrane. Its higher concentration in MMD patients suggests a possible autoimmune mechanism in MMD as the antibody could contribute to thrombus formation in strokes.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Bonduel et al (5) reported that prothrombotic disorders were detected in 4 out of 10 non-Japanese children with Moyamoya. In their series, inherited PSD was found in 1 patient; LA and ACA were detected in the remaining 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oral anticoagulation is recommended if there is isolated PSD because of the possibility of a recurrent thrombosis. However, prophylactic oral anticoagulation is controversial in MMS patients with PSD due to the risk of intracranial haemorrhage (5,6). Because of PIVH, we postponed anti-coagulation in the acute stage.…”
Section: Discussionmentioning
confidence: 99%
“…10,14) Moyamoya syndrome may include inherited disorders such as Down syndrome, 5) neurofibromatosis 1, 9) and protein C deficiency, 7) as well as other acquired pathological conditions which may be involved in the mechanisms causing such moyamoya phenomena. [1][2][3] Autoimmune mechanisms such as Grave's disease, 3) Behcet's disease, 6) and antiphospholipid syndrome 1) may also be involved in the development of moyamoya syndrome, although cross-reactivity of autoantibodies to cerebral vessels has not yet been clearly demonstrated. Genetic factors may also contribute as the possible locations of genes for familial moyamoya disease have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%